Motility of Amphistegina lobifera throughout the 6-week BEA experiment - Christiane Schmidt; Diana N Puerto Rueda; Moritz Nusser; Clinton A Oakley; Xavier Pochon; Marleen Stuhr; Débora Raposo; Simon K Davy (PANGAEA, 2025)
This dataset records the motility of the foraminifera species Amphistegina lobifera observed over the 6-week Menthol Concentration Comparison (MCC) experiment. It includes data on the number of foraminifera attached to the walls of the culturing jar and potential changes in motility over time under specific experimental conditions.
In: Schmidt, C et al. (2025): Menthol-DCMU bleaching experiments on two foraminifera species, Amphistegina lobifera and Sorites orbiculus [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974618